Ecological management of agricultural weeds - Liebman, Matt (Cambridge University Press, 2001)
This volume provides principles and practices for ecologically based weed management in a wide range of temperate and tropical farming systems. The authors describe how tillage and cultivation practices, manipulations of soil conditions, competitive cultivars, crop diversification, grazing livestock, arthropod and microbial biocontrol agents, and other factors can be used to reduce weed germination, growth, competitive ability, reproduction, and dispersal. Special attention is given to the evolutionary challenges that weeds pose and the roles that farmers can play in the development of new weed management strategies